On improved image encryption scheme based on chaotic map lattices - JASTRZĘBSKI, K.; KOTULSKI, Z. (Engineering Transactions, 2009)
In this paper we examine one of the recently proposed chaotic image encryption algorithms, based on chaotic map lattices (CML). We show certain problems with the chaotic map, as well as errors in the designed algorithm. Then we propose a way to improve it and present a new version of algorithm and its implementation. At the end, we show the results of a security analysis and a comparison of both schemes. These results were obtained in the MSc Thesis.